Comparison of Real-world Outcomes Between Patients Treated with Tapentadol ER or Oxycodone CR - Mike Durkin; Jacqueline Pesa; Jessica Lopatto; Rachel Halpern; Damon Van Voorhis; Stephanie Korrer (Journal of Health Economics and Outcomes Research)
**Background:** The objective of this study was to compare health care utilization and costs between matched cohorts of chronic pain patients treated with the opioids tapentadol extended release (ER) or oxycodone controlled release (CR).